(untitled) (Rudarsko-geološko-naftni zbornik, 2025)
The propagation of waves generated by an explosion induces both tensile and compressive stresses in the rock, impacting its mechanical and dynamic behaviour and ultimately leading to failure. Within this process, the phenomenon of crack expansion is of significant importance and has garnered the attention of various researchers in recent years. Predicting fracture geometry in rock materials, particularly in the context of crack growth, is a complex problem often necessitating advanced techniques. In this study, a blast hole was drilled into a concrete sample, and four explosion modes were examined using the discrete element method. These modes included the simultaneous modelling of shock energy, reflection, and gas pressure; the simultaneous modelling of shock energy and gas pressure; the simultaneous modelling of shock energy and reflection; and the modelling of shock energy alone. While the homogeneity observed in artificial samples like concrete may not precisely mimic that of stone samples, the findings of such research remain valuable within their limitations. The results indicate that the highest joint density, or, in other words, the most substantial rock fragmentation, occurs when all three types of shock energy, reflection, and gas pressure are present simultaneously. Furthermore, the results show that the model incorporating both gas pressure and shock energy exhibits the most significant rock fragmentation, followed by the model considering only shock and reflection energy. Finally, the model modelling shock energy alone demonstrates the least fragmentation.